2013
DOI: 10.1111/ijd.12016
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous porphyrias part II: treatment strategies

Abstract: The porphyrias are diverse in pathophysiology, clinical presentation, severity, and prognosis, presenting a diagnostic and therapeutic challenge. Although not easily curable, the dermatological manifestations of these diseases, photosensitivity and associated cutaneous pathology, can be effectively prevented and managed. Sun avoidance is essential, and patient education regarding the irreversibility of photocutaneous damage is a necessary corollary. Beyond preventative measures, the care of fragile, vulnerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 205 publications
(415 reference statements)
0
14
0
1
Order By: Relevance
“…This occurs predominately at wavelengths 400‐410 nm (the Soret band) as well as 4 additional absorption bands of decreasing intensity in the range of 500‐700 nm. Absorption at these wavelengths cause porphyrins to produce singlet oxygen molecules that form free radicals in tissue and lead to oxidative damage . In addition, Lim proposed that photoactivation of the complement system with uroporphyrin leads to the activation of mast cells and the release of proteases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs predominately at wavelengths 400‐410 nm (the Soret band) as well as 4 additional absorption bands of decreasing intensity in the range of 500‐700 nm. Absorption at these wavelengths cause porphyrins to produce singlet oxygen molecules that form free radicals in tissue and lead to oxidative damage . In addition, Lim proposed that photoactivation of the complement system with uroporphyrin leads to the activation of mast cells and the release of proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption at these wavelengths cause porphyrins to produce singlet oxygen molecules that form free radicals in tissue and lead to oxidative damage. 2 In addition, Lim 11 proposed that photoactivation of the complement system with uroporphyrin leads to the activation of mast cells and the release of proteases. These proteases cause dermal-epidermal separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological approaches have included pharmaceutical-grade b-carotene, narrow wave UVB phototherapy, cysteine, afamelanotide, antihistamines, and vitamin C (Table 1) (Sawyer et al, 1980;Krook and Haeger-Aronsen, 1982;Mathews-Roth et al, 1994;Collins and Ferguson, 1995;Warren and George, 1998;Wahlin et al, 2011a;Fabrikant et al, 2013;Tintle et al, 2014;Biolcati et al, 2015;Langendonk et al, 2015;Lengweiler et al, 2015;Minder and Schneider-Yin, 2015). Minder et al (2009) reviewed the treatment options for dermal photosensitivity in EPP in 2009 and concluded that the data were insufficient to prove efficacy of any treatments studied in EPP.…”
Section: Clinical Manifestations and Management Of Ppix Toxicitymentioning
confidence: 99%
“…Phototoxicity is relatively common in patients prescribed photoactive drugs and is the basis for photodynamic therapy (PDT) [19,27,28,38]. Phototoxicity also occurs in the light-exposed skin of patients suffering from erythropoietic protoporphyria (EPP) in whom the photoactive molecule protoporphyrin IX (PpIX) accumulates [18,36]. When exposed to light, fluorescent molecules generate reactive singlet oxygen ( 1 O 2 ) from triplet oxygen by a type two reaction and free radicals, such as superoxide, by a type one reaction [12].…”
Section: Introductionmentioning
confidence: 99%